As interpretacoes sobre oncocercose dos Yanomami da Comunidade Arathaú desde 2000 até 2008 - Merces Schuertz, Joana Claudete Das (2012)
This work aims to ascertain the perception of yanomami on Onchocerciasis of the natives of Arathaú. It was based upon the importance of anthropological knowledge in indigenous communities. The Onchocerciasis has been identified in Brazil at the beginning of the decade 1970, in the Yanomami territory. At the present time, although it remains restricted area. The Brazilian Program is committed to the effort of Latin American Elimination of Onchocerciasis. Since 1997, parasitological surveys were conducted in this area of Arathaú; this area has shown us hiperendemic. However, the contact and the presence of non-indigenous resulted from various endemic diseases, malária, tuberculosis, and Onchocerciasis. The main objective of this study is to analyze what is the Yanomami vision and knowledge on Onchocerciasis, as they have responded to the treatment of disease, and how interference in their culture. The history of social representations of health and disease mentions the natural and supernatural elements that inhabit such representations, causing the senses and spread into culture, the spirits, values and beliefs of the people. In this context, the disease has its representation associated with feelings of guilt, fear, superstitions, mysteries. This experiment depends on what is meant by disease and how it is interpreted. Through this work such data can guide the rest of the team of health professionals that is providing assistance to health there.